Geografia dos Votos Inválidos na Eleição de 1982 no Estado do Rio de Janeiro - Sant'Anna, Marina; Freire, Ludy (Anuário do Instituto de Geociências, 1984)
Firstly this paper tries to analyze and explain the spatial distribution pattern of null and blank votes across the territorial administrative divisious (municipios) of Rio de Janeiro State in 1982 election. Secondly, it tries to identify and evaluate the correlation between void votes and the social-economic characteristcs of the population of these municipios.